Multidisciplinary Management of Rectal Cancer Questions and Answers - Valentini, Vincenzo; Schmoll, Hans-Joachim.; Velde, Cornelis J. H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book seeks to promote an integrated approach among the various specialists involved in the management of rectal cancer with a view to ensuring that treatment is tailored appropriately to the individual patient. For ease of use, a question and answer format is employed. The focus is on those issues typically confronted during daily clinical practice in relation to risk factors, imaging, surgery, radiotherapy, and chemotherapy. The services of an outstanding panel of authors representative of the major European oncological societies have been acquired in order to formulate the questions and provide the answers. All who need assistance in addressing concerns that arise from the need for multidisciplinary management of rectal cancer will find the book to be an ideal source of helpful information.
Introduction -- What do we consider cancer of the rectum? -- What is considered state of the art in rectal cancer by ESTRO, ESMO and ESSO? -- Q&As on Risk Factor Identification -- Q&As on Imaging -- Q&As on Radiotherapy -- Q&As on Chemotherapy -- Q&As on Surgery -- Q&As on Pathology -- Q&As on Multidisciplinary Team Management.
Keywords: Medicine; Radiology, Medical; Radiotherapy; Oncology; Cancer -- Surgery; Pathology; Medicine & Public Health; Oncology; Surgical Oncology; Radiotherapy; Diagnostic Radiology; Pathology